Use of organic acids and a competitive exclusion product as growth promoter and salmonella enteritidis control in commercial Turkeys - Milbradt, E. L. [UNESP]; Okamoto, A. S. [UNESP]; Padovani, C. R. [UNESP]; Fascina, V. B. [UNESP]; Silva, T. M. [UNESP]; Altarúgio, R. [UNESP]; Hataka, A. [UNESP]; Schmidt, E. M.S. [UNESP]; Andreatti Filho, R. L. [UNESP] (FapUNIFESP (SciELO), 2017)
It is estimated that Salmonella causes one million illnesses in the United States annually, with 19,000 hospitalizations and 380 deaths. There are various serotypes of this bacterium, and the serotypes Typhimurium and Enteritidis are commonly isolated from outbreaks and, in most cases, present resistance to the antibiotics utilized in clinical medicine. One of the current theories to explain the emergence of bacterial resistance is the continuous use of antibiotics as growth promoters in animal feeds. Despite the lack of evidences that antibiotic growth promoters cause bacterial resistance, the poultry industry has explored strategies to reduce or to eliminate the use of antibiotic growth promoters in the production chain, including the improvement of biosecurity programs, use of vaccines, genetic selection, and the feeding of other additives, such as organic acid blends (OAB) and competitive exclusion (CE) products. This study aimed at evaluating the effect of the continuous dietary supplementation of an OAB and a CE product on the growth performance, pH of the crop and cecal contents, control of Salmonella Enteritidis (SE) in the cecal content, and acutephase protein serum levels in starter commercial turkeys. The additives promoting similar results as antibiotics under controlled experimental conditions should be further evaluated on commercial farms to allow their utilization under practical conditions. Supplementing commercial turkey diets with the evaluated OAB and CE product may reduce SE load. Serum OVT and AGP levels can be used as effective and fast indicators of infection, including that by SE.
Keywords: Commercial turkey; Competitive exclusion; Organic acid; Salmonella Enteritidis